Correlation between cephalometric data and severity of sleep apnea - Vanessa Gonçalves Silva; Laíza Araújo Mohana Pinheiro; Priscila Leite da Silveira; Alexandre Scalli Mathias Duarte; Ana Célia Faria; Eduardo George Baptista de Carvalho; Edilson Zancanella; Agrício Nubiato Crespo (Brazilian Journal of Otorhinolaryngology, 2014)
INTRODUCTION: Obstructive sleep apnea syndrome has a high prevalence among adults. Cephalometric variables can be a valuable method for evaluating patients with this syndrome. OBJECTIVE: To correlate cephalometric data with the apnea-hypopnea sleep index. METHODS: We performed a retrospective and cross-sectional study that analyzed the cephalometric data of patients followed in the Sleep Disorders Outpatient Clinic of the Discipline of Otorhinolaryngology of a university hospital, from June 2007 to May 2012. RESULTS: Ninety-six patients were included, 45 men, and 51 women, with a mean age of 50.3 years. A total of 11 patients had snoring, 20 had mild apnea, 26 had moderate apnea, and 39 had severe apnea. The distance from the hyoid bone to the mandibular plane was the only variable that showed a statistically significant correlation with the apnea-hypopnea index. CONCLUSION: Cephalometric variables are useful tools for the understanding of obstructive sleep apnea syndrome. The distance from the hyoid bone to the mandibular plane showed a statistically significant correlation with the apnea-hypopnea index.